2013
DOI: 10.1371/journal.pone.0052813
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Ranges of Immature African White-Backed Vultures (Gyps africanus) and Their Use of Protected Areas in Southern Africa

Abstract: Vultures in the Gyps genus are declining globally. Multiple threats related to human activity have caused widespread declines of vulture populations in Africa, especially outside protected areas. Addressing such threats requires the estimation of foraging ranges yet such estimates are lacking, even for widespread (but declining) species such as the African white-backed vulture (Gyps africanus). We tracked six immature African white-backed vultures in South Africa using GPS-GSM units to study their movement pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 44 publications
7
77
5
Order By: Relevance
“…For instance the average movement recorded in the Serengeti was 51 km and in Kruger 34 km (Mundy et al, 1992). A more recent study of immature African Whitebacked Vultures showed a mean distance travelled per day of 33.39 km (Phipps et al, 2013). It has been noted that, while nesting without a chick, the birds can fly over 240 km between the nest and a carcass and this is consistent with our value of 260 km (Houston & Cooper, 1975).…”
Section: Discussionsupporting
confidence: 91%
“…For instance the average movement recorded in the Serengeti was 51 km and in Kruger 34 km (Mundy et al, 1992). A more recent study of immature African Whitebacked Vultures showed a mean distance travelled per day of 33.39 km (Phipps et al, 2013). It has been noted that, while nesting without a chick, the birds can fly over 240 km between the nest and a carcass and this is consistent with our value of 260 km (Houston & Cooper, 1975).…”
Section: Discussionsupporting
confidence: 91%
“…Scavengers, for example, can be reliant on carcases of livestock or companion animals for food, often from landfills or provided as a conservation measure. This brings with it the potential for exposure to veterinary drugs used to treat domesticated animals [14,65]. For example, residues of barbiturates in carrion of euthanized pets have been found to exceed the lethal dose for a spectrum of scavengers and there have been reports of secondary barbiturate poisoning [14].…”
Section: How Can We Predict Environmental Risk?mentioning
confidence: 99%
“…Livestock graze throughout the species' foraging range and are scavenged from communal grazing lands in Lesotho or commercial livestock farms in South Africa, whereas wild ungulates are scavenged predominantly from protected areas. Related to our food shortage hypothesis, we also investigated whether the presence of more predictable food resources, in the form of supplementary feeding sites, influences territory occupancy because many other vulture populations have been found to be heavily reliant on supplementary feeding (Piper 2005, Deygout et al 2009, Cortés-Avizanda et al 2010, Phipps et al 2013. Although livestock and wild ungulate density is an indirect measure of food availability, we used this as a surrogate for the availability of carrion and predicted that if food supply influences territorial occupancy then it would be positively related to the number of ungulates and the presence of supplementary feeding sites in the landscape.…”
Section: Introductionmentioning
confidence: 99%